2017
DOI: 10.1634/theoncologist.2016-0308
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study on Effect of Short-Term Periodic Steroid Premedication on Bone Metabolism in Gastrointestinal Cancer (ESPRESSO-01)

Abstract: This study is an evaluation of the effect of gastrointestinal cancer chemotherapy with short‐term periodic steroid premedication on bone metabolism. Primary endpoints were changes in bone mineral densities and metabolic bone turnover 16 weeks after initiation of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 54 publications
0
17
1
2
Order By: Relevance
“…Effective approaches to reduce patients’ exposure to steroids remain among the hot topics in clinical research on CINV. Recent evidences from prospective studies highlighted a potentially detrimental impact of short‐term prophylactic dexamethasone in patients undergoing consecutive courses of emetogenic chemotherapy . Aapro et al compared the efficacy of palonosetron when administered alone or in combination with 1‐day dexamethasone, in post hoc analyses of two studies on CINV in patients undergoing MEC; they reported that the proportion of nausea was lower in patients treated with the 1‐day dexamethasone regimen over a 5‐day period .…”
Section: Discussionmentioning
confidence: 99%
“…Effective approaches to reduce patients’ exposure to steroids remain among the hot topics in clinical research on CINV. Recent evidences from prospective studies highlighted a potentially detrimental impact of short‐term prophylactic dexamethasone in patients undergoing consecutive courses of emetogenic chemotherapy . Aapro et al compared the efficacy of palonosetron when administered alone or in combination with 1‐day dexamethasone, in post hoc analyses of two studies on CINV in patients undergoing MEC; they reported that the proportion of nausea was lower in patients treated with the 1‐day dexamethasone regimen over a 5‐day period .…”
Section: Discussionmentioning
confidence: 99%
“… 23 Thus, in patients who develop acute CINV, dexamethasone may be useful in preventing nausea and anorexia in the delayed phase. However, because dexamethasone has several side effects, including insomnia, indigestion/epigastric discomfort, agitation, and increased appetite, 24 , 25 we need to be mindful of these side effects when using dexamethasone for delayed antiemetic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Bone metabolism in women differs from that in men because of differences in endocrinological factors, physical activity, and diet. Furthermore, the previous study demonstrated anticancer agents influenced bone metabolism [13]. The only previous prospective study that reported on changes in BMD after gastric cancer surgery enrolled not only men, but also women, and some patients received adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%